Pengaruh Tingkat Keuntungan Pasar, Nilai Tukar Rupiah, Inflasi, Dan Tingkat Suku Bunga, Terhadap Return Saham Industri Food And Baverage Tahun 2007-2009 Studi Pada Bursa Efek Indonesia - Rina Zulelli; Meina Wulansari Yusniar (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
Return is the profit in the future which is compensation for the risk associated with the investments made. One instrument is a capital investment in the stock market. The purpose of this study to examine the effect of macroeconomic variables (market profit rate, exchange rate, inflation, interest rates) to the Food and Baverage stock returns.The samples in this study were shares in food and industrial sectors baverage listed on the Stock Exchange in the period 2007- Sampling using purposive sampling and obtain samples 17 companies. Data taken from the financial statements issued by a public company listed on the Indonesia Stock Exchange (IDX). Analysis of the data in this study using multiple regression with teory Arbitrage Price Theory (APT). The results of the study by testing the coefficient of determination (R square) concluded baverage food and stock returns can be explained by the four independent variables (macroeconomic Variebel) of 23.3%. F test results in this study indicate that macroeconomic variables (market profit rate, exchange rate, inflation and interest rate) as a whole has significant influence.T test results in this study indicate that the variable profit rate, exchange rate, inflation has no significant effect, while interest rates have a significant effect on the Food and Baverage stock returns